2014
DOI: 10.1016/j.jsat.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of Web-based videoconferencing for substance abuse counseling

Abstract: Web-based videoconferencing can improve access to substance abuse treatment by allowing patients to receive counseling services in their homes. This randomized clinical trial evaluates the feasibility and acceptability of web-based videoconferencing in community opioid treatment program (OTP) participants. Participants that reported computer and Internet access (n = 85) were randomly assigned to receive 12 weeks of weekly individual counseling in-person or via eGetgoing, a web-based videoconferencing platform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 29 publications
2
92
0
1
Order By: Relevance
“…Results of this study contribute to the growing literature suggesting that telehealth approaches may be effective tools for reducing barriers to care for isolated, vulnerable populations (King, Brooner, Peirce, Kolodner, & Kidorf, 2014;Litvin, Abrantes, & Brown, 2013). Many poor, older, and less mobile people, and those living in rural areas, are unable to meet regularly with service providers due to the difficulties of getting to a clinic or office.…”
Section: Application To Substance Abuse Treatment For Older Adultsmentioning
confidence: 91%
“…Results of this study contribute to the growing literature suggesting that telehealth approaches may be effective tools for reducing barriers to care for isolated, vulnerable populations (King, Brooner, Peirce, Kolodner, & Kidorf, 2014;Litvin, Abrantes, & Brown, 2013). Many poor, older, and less mobile people, and those living in rural areas, are unable to meet regularly with service providers due to the difficulties of getting to a clinic or office.…”
Section: Application To Substance Abuse Treatment For Older Adultsmentioning
confidence: 91%
“…14 Results of the study showed no differences in the percentage of positive drug screens or compliance to attending the counseling sessions. 14 The study concluded that the use of videoconference is a feasible alternative to in-person counseling for patients with opioid dependence. 14 …”
Section: Videoconferencing For Substance Abuse Counselingmentioning
confidence: 98%
“…14 The study concluded that the use of videoconference is a feasible alternative to in-person counseling for patients with opioid dependence. 14 …”
Section: Videoconferencing For Substance Abuse Counselingmentioning
confidence: 98%
“…Neste sentido, no campo das intervençÔes por internet, uma questĂŁo importante que permeia as investigaçÔes recentes relaciona-se Ă  formação da aliança terapĂȘutica nesta modalidade de psicoterapia e se ela poderia ser comparada com a psicoterapia presencial (Anderson et al, 2012;King, Brooner, Peirce, Kolodner, & Kidorf, 2014). RevisĂ”es de literatura tĂȘm abordado este assunto nos Ășltimos anos (Simpson, & Reid, 2014;Sucala et al, 2012), mas nĂŁo foram encontradas revisĂ”es que investigassem a aliança terapĂȘu-tica na TCC por videoconferĂȘncia.…”
Section: Introductionunclassified